2020
DOI: 10.1038/s41467-020-19037-9
|View full text |Cite
|
Sign up to set email alerts
|

MIR2111-5 locus and shoot-accumulated mature miR2111 systemically enhance nodulation depending on HAR1 in Lotus japonicus

Abstract: Legumes utilize a shoot-mediated signaling system to maintain a mutualistic relationship with nitrogen-fixing bacteria in root nodules. In Lotus japonicus, shoot-to-root transfer of microRNA miR2111 that targets TOO MUCH LOVE, a nodulation suppressor in roots, has been proposed to explain the mechanism underlying nodulation control from shoots. However, the role of shoot-accumulating miR2111s for the systemic regulation of nodulation was not clearly shown. Here, we find L. japonicus has seven miR2111 loci, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 69 publications
1
39
0
Order By: Relevance
“…To optimize this symbiosis, legumes control nodule numbers using long-distance negative/positive feedback systems in response to rhizobial infection and soil nutrient availability (Caetano-Anollés and Gresshoff, 1991;Ferguson et al, 2019). Accumulating evidence suggests that shoot-derived miR2111 might play a central role in controlling nodule numbers (Tsikou et al, 2018;Gautrat et al, 2020a;Okuma et al, 2020;Zhang et al, 2021). Here, we summarize recent advances in the study of systemic regulation of nodulation in response to external environmental stimuli, particularly focusing on the relevance of shoot-derived miR2111.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize this symbiosis, legumes control nodule numbers using long-distance negative/positive feedback systems in response to rhizobial infection and soil nutrient availability (Caetano-Anollés and Gresshoff, 1991;Ferguson et al, 2019). Accumulating evidence suggests that shoot-derived miR2111 might play a central role in controlling nodule numbers (Tsikou et al, 2018;Gautrat et al, 2020a;Okuma et al, 2020;Zhang et al, 2021). Here, we summarize recent advances in the study of systemic regulation of nodulation in response to external environmental stimuli, particularly focusing on the relevance of shoot-derived miR2111.…”
Section: Introductionmentioning
confidence: 99%
“…STTM lines of miR2111 led to an increased level of TML and decreased nodulation. Additionally, knockout lines of MIR2111‐5 showed a decrease in nodule number similar to the STTM lines of miR2111 (Okuma et al, 2020). GUS staining revealed that miR2111 expresses in leaves but not in root.…”
Section: Mobile Mirnas and Control Of Symbiosismentioning
confidence: 88%
“…Overexpression of miR2111c resulted in hyperinfection and an enhanced number of nodules at 21 dpi. Another recent study by Okuma, Soyano, Suzaki, & Kawaguchi, 2020, reported that miR2111‐5 loci in L. japonicus has high expression in leaves and its expression decreases upon rhizobial infection in Hypernodulation aberrant root1 ( HAR1 ) dependent manner (Okuma et al, 2020). STTM lines of miR2111 led to an increased level of TML and decreased nodulation.…”
Section: Mobile Mirnas and Control Of Symbiosismentioning
confidence: 99%
“…Mobile small RNAs may coordinate events in distant plant parts. For example, several miRNAs are induced in shoots and transported to roots to regulate responses to nutrient starvation and nodulation (Buhtz et al, 2010;Lin et al, 2008;Okuma et al, 2020;Pant et al, 2008). Several mobile small RNAs, such as miR165/6, miR394, and the trans-acting siRNA tasiR-ARF, serve as morphogenic signals that pattern cell fates in development (Carlsbecker et al, 2010;Chitwood et al, 2009;Knauer et al, 2013;Miyashima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile small RNAs may coordinate events in distant plant parts. For example, several miRNAs are induced in shoots and transported to roots to regulate responses to nutrient starvation and nodulation (Buhtz et al, 2010;Lin et al, 2008;Okuma et al, 2020;Pant et al, 2008). Several mobile small RNAs, such as miR165/6, miR394, and the trans-acting .…”
Section: Introductionmentioning
confidence: 99%